Concepções de língua e sujeito no livro didático de língua inglesa - Azevedo, Lúcia Maria Castroviejo (2013)
This research in Master Level had as primordial focus to analyze the language and subject conceptions found in the hidden discursivities into two didactic books. The Links: English for teens and Keep in mind, the first written by Denise Santos and Amadeu Marques and the second by Elizabeth Young Chin and Maria Lúcia Zaorob, both from the 6th period and approved by MEC to be used since 2011until 2013 in the Basic Education. The research is based in Applied Linguistics theory related with Dialogic Discourse Analysis and French Discourse Analysis. These theories gave me support with elements to answer some questions about the process of foreign language learning-teaching and the role of didactic book in this process. Language and subject representations were analyzed as they build and after break (by themselves) and which were the denial, deletion effects from the discursivities produced by structure exercises, heading and illustration (verbal and non-verbal language) extracted from English language didactic book. I understand that to investigate these discursivities, I could better understanding the didactic book role in English learning-teaching process as I reflected about discourses which surround in this didactic resource that build images that resulted in representations of social-cultural-ideological identity that frequently are not recognized among/by inbuilt subject in English Language in the classroom event. Into the analysis, cuts were made to establish a methodological order, i) from didactic book summary/index structure I did a macro analysis, ii) from all units fragments which regularities were selected I did a microanalysis when I investigated the language and subject conceptions hidden in the English language didactic book, I had the perception that this material still showed homogeneous, clear, abstract language conception and a passive subject, unique, by repetitive automaton that does not get reflection. The exercises are standard, the thematic units are typified by the stratified contents organization protected from world concept variation and values that do not allow the learner of this language solve the daily problems. Therefore to reflect them, this material became, in this way, a disciplinary exercise created by repetition and by subject homogeneity; it establish a chain between the knowledge and didactic system pedagogic process that define by itself into a naïve perspective to be considered as essential. Is brings a true discourse, underlying by a content that take far from the language production and not from nits formation and creativity. The English language didactic books analyzed by this reason gave a total illusion of a learn subject in this meaning about this learning process, in this case, they are obeyed, pre- established and absorbed in their unique voice.